Social Media User’s Engagement’s Function And Measurements On Marketing Communication 4.0 - Bogie Wardana Satriyonegoro; Niken Febrina Ernungtyas (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
In the era of Industry 4.0, social media user engagement contributed to the effectiveness of marketing communications. Companies that use social media as communication marketing channels are still trying to define the concept of engagement according to the subjective understanding and definition of measurement offered by social media insights. This article provides an update on the concept of social media user engagement in the context of marketing communication in Indonesia. Through a qualitative approach to the study of literature and interviews with some informants who use social media as a marketing communication platform, it was found that the involvement of social media users serves to measure and find patterns of content that are effectively used for marketing communication. In general, social media user engagement can also be grouped into three dimensions: affective, cognitive, and behavioral engagement.